(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
The data encoding and decoding schemes are used to reduce the power dissipation of the communication system in a Network-on-Chip (NoC). A NoC comprises routers and interconnections allowing communication between the PEs.The self-switching and coupling-switching actions are caused for link power dissipation. The end to end basis have been proposed data encoding and decoding schemes are mainly working at flit level ;which allows us to reduce the both self and coupling switching activities. The scheme uses the binary to gray translation at the transmitter and gray to binary translation at the receiver. The self-switching is reducing by checking the switching transition and then the coupling system is included with the wormhole routed network. The proposed scheme has maximum power consumed is 2.2mW the design of encoder and decoder architecture the performance in various kind of scheme have to be analyzed and to obtain the end to end scheme.